The Bruce B. Lawrence reader : Islam beyond borders - Lawrence, Bruce B. (Duke University Press, 2021)
"This Reader assembles over two dozen selection of writing by leading scholar of Islam Bruce B. Lawrence which range from analyses of premodern and modern Islamic discourses, practices, and institutions to methodological and theoretical reflections on the study of religion."--